A Polymer Blend Substrate for Skeletal Muscle Cells Alignment and Photostimulation. Issue 2 (18th December 2020) - Vurro, Vito; Scaccabarozzi, Alberto Davide; Lodola, Francesco; Storti, Filippo; Marangi, Fabio; Ross, Aaron Michael; Paternò, Giuseppe Maria; Scotognella, Francesco; Criante, Luigino; Caironi, Mario; Lanzani, Guglielmo
Abstract : Substrate engineering for steering cell growth is a wide and well‐established area of research in the field of modern biotechnology. Here we introduce a micromachining technique to pattern an inert and transparent polymer matrix blended with a photoactive polymer. We demonstrate that the obtained scaffold combines the capability to align with that to photostimulate living cells. This technology can open up new and promising applications, especially where cell alignment is required to trigger specific biological functions, e.g., generate powerful and efficient muscle contractions following an external stimulus. Abstract : A multifunctional polymer based substrate able to apply morphological and optical stimulation is presented in the article. The alignment and photostimulation effect are studied on skeletal muscle as a proof of concept for tissue engineering application.